Pathogenicity and innate response to Avibacterium paragallinarum in chickens - Mengjiao Guo (Elsevier, 2022)
ABSTRACT: Infectious coryza (IC) is an acute infectious upper respiratory disease in chickens. Recently, the prevalence of IC has increased in China. In this study, to clarify the pathogenic mechanism and innate immune response of Avibacterium paragallinarum (A. paragallinarum), an infection experiment with A. paragallinarum was conducted. Our results showed that the whole course of IC was approximately 7 d. The clinical signs score was highest at 3 dpi and decreased from 5 dpi. A large amount of mucus and exudates was found in the infraorbital sinuses and nasal cavity. The A. paragallinarum contents in blood remained the highest, reaching 9.16 × 105 CFU/g at 5 dpi, which indicated that A. paragallinarum could rapidly invade the host, replicate in the blood and cause bacteremia. A. paragallinarum targets the upper respiratory tract. The infiltration of inflammatory cells, macrophages, and heterophilic granulocytes was only observed in the nasal cavity and infraorbital sinus. The Tlr4 and Nod1 pathways were activated and induced proinflammatory responses in chickens after infection with A. paragallinarum. The expression of Il1β and Il6 in the nasal cavity was significantly higher than that in the spleen, and it was consistent with the gross lesions and pathological changes. In particular, the expression of Il6 increased 229.07-fold at 1 dpi in the nasal cavity and increased 3.12-fold in the spleen. The high level of proinflammatory cytokines in the nasal cavity at an early stage of infection may be the main factor related to acute upper respiratory inflammation in chickens. These findings provide a reference for the occurrence and development of diseases mediated by A. paragallinarum.